Comprehensive study of current trend of the remotely operated vehicle for underwater systems - Fauzal Naim Zohedi; Mohd Shahrieel Mohd Aras; Hyreil Anuar Kasdirin (Universitas Ahmad Dahlan, 2022)
This paper aim to provide a basic fundamental knowledge for researchers on underwater remotely operated vehicle (ROV) system and current trend of ROV controller. The vehicle is used for exploration, investigation or inspection of underwater environment as a replacement of human due to human limitation. It can dive deeper than human and can be manoeuvred into hazard environment. In this paper, the basic development and classification of ROV is discussed. The modelling of ROV, manoeuvrability and controller designed by researchers since 1990 also being discussed. It is expected that this paper will help readers in doing research on the controller of ROV.